2019
DOI: 10.12659/msm.915419
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Exosomal AGAP2-AS1 (AGAP2 Antisense RNA 1) In Breast Cancer Cells Inhibits Trastuzumab-Induced Cell Cytotoxicity

Abstract: Background Trastuzumab therapy is important for patients with HER2-positive breast cancer, but more and more patients have experienced trastuzumab resistance during recent years. Accumulating evidence from recent studies showed that long non-coding RNAs (lncRNAs) play essential roles in chemoresistance of various cancer types, but the precise role of lncRNAs in trastuzumab resistance is unclear. In the present study, we aimed to identify the biofunction of lncRNA APAP2-AS1 in tranastuzumab resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 32 publications
1
52
0
Order By: Relevance
“…Also, the exosomal expression of lncRNA-SNHG14 in serum was highly upregulated in patients who exhibited resistance to trastuzumab compared with patients who responded to trastuzumab 66 . Similarly, the lncRNA AGAP2 antisense RNA 1 (AGAP2-AS1)-containing exosomes also enhanced trastuzumab resistance in BC cells 67 . The heterogeneous nuclear ribonucleoprotein A2B1 (hnRNPA2B1), an RNA-binding protein, was found essential in loading lncRNA AGAP2-AS1 into exosomes 68 .…”
Section: Exosome and Hormonal Resistance In Bcmentioning
confidence: 99%
“…Also, the exosomal expression of lncRNA-SNHG14 in serum was highly upregulated in patients who exhibited resistance to trastuzumab compared with patients who responded to trastuzumab 66 . Similarly, the lncRNA AGAP2 antisense RNA 1 (AGAP2-AS1)-containing exosomes also enhanced trastuzumab resistance in BC cells 67 . The heterogeneous nuclear ribonucleoprotein A2B1 (hnRNPA2B1), an RNA-binding protein, was found essential in loading lncRNA AGAP2-AS1 into exosomes 68 .…”
Section: Exosome and Hormonal Resistance In Bcmentioning
confidence: 99%
“…Recent studies have reported that exosomes can also reduce the effects of chemotherapy via removal of chemotherapeutic drugs from tumor cells. For example, breast cancer cell-derived exosomes can reduce the effectiveness of trastuzumab, a first-line drug for advanced HER2-positive breast cancer patients; thus, removal of such exosomes from circulation could restore trastuzumab sensitivity in the breast cancer cells [ 199 ]. Therefore, exosomes are a major determinant for inducing or disseminating resistance phenotypes in anti-tumor therapy.…”
Section: Exosome Functions In Cancermentioning
confidence: 99%
“…97 AGAP2-AS1 decreases the cytotoxicity of TZB via being incorporated into exosomes, and promotes TZB resistance in BC. 98 AGAP2-AS1 inhibits cell apoptosis and promotes TZB resistance in BC cells by upregulating MyD88, which results from the enrichment of H3K27ac at the promoter region of MyD88, and activating the NF-ÎșB signaling pathway. 99 LncRNA TINCR is upregulated in HER-2+ BC cells; it sponges miR-125b and targets Snail-1, thereby promoting TZB resistance and the associated EMT process in BC cells.…”
Section: Trastuzumabmentioning
confidence: 99%
“…51 AGAP2-AS1 is incorporated into exosomes in an hnRNPA2B1-dependent manner, thereby decreasing TZB-induced cytotoxicity and promoting TZB resistance in BC cells. 98 SNHG14 promotes TZB resistance in sensitive BC cells via exosomes. 102 In addition to ceRNAs and exosomes, lncRNAs can regulate drug resistance in BC via cellular or molecular targets.…”
Section: Exosomesmentioning
confidence: 99%